Patient profiles contribute to differences in quality metrics of stroke centers - Ungerer, Matthias; Haji Begli, Nima; Heyse, Miriam; Purrucker, Jan; Regula, Jens Ulrich; Berberich, Anne; Ciolli, Ludovico; Nagel, Simon; Ringleb, Peter A.; Gumbinger, Christoph (Neurosciences, 2021)
Objectives: To examine this association by comparing patient profiles in 2 closely affiliated hospitals and by examining their association with quality metrics. - Methods: We performed a retrospective cohort study comparing a university level comprehensive stroke centers (CSC) with its teaching hospital and local stroke unit (LSU) using routinely collected quality assurance data over a 2 year period. Both hospitals were closely affiliated, shared important resources and medical staff rotated amongst both hospitals. We compared patient profiles as well as internationally recognized quality metrics and examined the association of profiles with quality metrics. - Results: A total of 2,462 patients were treated in the CSC and 726 in the LSU. The LSU had a longer door-to-image and door-to-needle times. Rate of systemic thrombolysis was lower in the LSU. Patient profiles differed significantly and were associated with door-to-image and door-to-needle times as well as intravenous thrombolysis rates, even when adjusted for stroke service level. The diagnostic procedures for stroke work-up were similar. Discharge management differed strongly. - Conclusion: Although LSUs and CSCs are the primary care providers in their respective regions, differences in patient profiles may contribute to differences in performance parameters. Adjusting for patient profiles may improve the comparability of the quality of stroke care provided by hospitals belonging to different stroke service levels.
Gesehen am 17.05.2021